2014
DOI: 10.5812/ijhrba.18932
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Educational Programs on Nutritional Behavior in Addicts Referring to Baharan Hospital, Zahedan (Eastern of IR Iran)

Abstract: Background:There are many factors which affect nutritional status of addicted such as lack o f knowledge, incorrect attitude toward modification of food pattern, and careless to food intake.Objectives:The aim of this study was to determine the effectiveness of educational program on nutritional behavior in addicts referring to Baharan hospital in Zahedan.Patients and Methods:Thirty-six addict patients were selected randomly. After recording general demographic data of patients, nutritional behaviors were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Concerning the educational level, the current finding revealed that nearly two-thirds of the substance user (64.9%) completed secondary education. This result was in the same line with Karajibani et al, (2014), who assumed that most addict patients had a medium level of education. Also, Abdel Naem, et al, (2020), indicated that 56% of participants graduated from a preparatory and technical school.…”
Section: Discussionsupporting
confidence: 85%
“…Concerning the educational level, the current finding revealed that nearly two-thirds of the substance user (64.9%) completed secondary education. This result was in the same line with Karajibani et al, (2014), who assumed that most addict patients had a medium level of education. Also, Abdel Naem, et al, (2020), indicated that 56% of participants graduated from a preparatory and technical school.…”
Section: Discussionsupporting
confidence: 85%
“…In fact, binge eating and weight gain were associated with relapse, especially among females [48,49]; and lack of sleep may be bidirectional: drug use causes sleep disturbances and difficulty sleeping causes relapse [50]. Thus, providing person-centered interventions including personal coaching in rehabilitation centers by way of preventing relapse are suggested as essential components in treatment facilities [51,52].…”
Section: Plos Onementioning
confidence: 99%
“…Effective measures for controlling food intake may include pairing nutritional programs with leisure/vocational activities, to establish healthy eating behavious while simultaneously increasing self-worth through actively working with individuals and identifying skills and vocations effaced during addiction. Further, establishing nutrition educational programs with emphasis on increasing knowledge, and changing attitudes and practices to promote positive nutrition behaviour [26,51] could help preventing relapse [55].…”
Section: Plos Onementioning
confidence: 99%
“…These hunger sensations can mimic the craving for opioids, when in fact, they are just hungry (Morley, Levine, Yim, & Lowy, 1983). On the other hand, some individuals may replace their obsession with opioids with that of sweet taste rewards (e.g., donuts), which can result in weight gain (Karajibani et al, 2014). This is often referred to as addiction transfer or addictive switch , whereby an individual trades one compulsive behavior for another (Brunault et al, 2015).…”
Section: Role Of Nutrition In Treatment and Recoverymentioning
confidence: 99%